Neonatal resuscitation at the Peripheral clinic - J.V. Larsen (AOSIS, 1979)
The low APGAR baby delivered in a clinic presents the midwife with a formidable problem. The problem arises from the fact that clinics generally are poorly equipped for major resuscitation of the newborn. The problem is further compounded by the fact that the baby with a low APGAR score travels very badly. He becomes hypothermic easily, and is likely to die if moved in a cold ambulance without oxygen or adequate heating. Then too, midwives are generally poorly trained for the task o f resuscitating babies suffering from severe asphyxia neonatorum, because they received their training in hospitals with the basic assumption that a medical officer is always in the background ready to take over the management of such problems. Finally, acceptance by the community of clinic-based obstetric services is largely dependent upon the clinics' achieving a nil perinatal mortality rate. The delivery of a gasping newborn who dies in the midwife's hands can do great damage to the reputation of the service.